Anti-inflammatory action of pequi oil associated to ultrasound in tendinitis in rats: macroscopic and histological analysis - Silva, Luiz Fernando Batista Pereira da; Poty, Josefa Angélica Cerqueira; Martins, Marcelino; Coelho, Nayana Pinheiro Machado de Freitas; Filho, Antônio Luiz Martins Maia; Costa, Charllyton Luis Sena da (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Repeated overloads of a tendon may give rise to an inflammatory response, called tendinitis, which usually begins suddenly. Researches report that the Brazilian Northeast is common to use the pequi oil (Caryocar Coriaceum wittm) in the treatment of inflammation and other diseases. Objective: To evaluate the anti-inflammatory effect of pequi oil in tendon repair process in rats after induced tendinitis. Methods: 36 male rats were divided into groups: control, ultrasound + oil pequi and pequi oil. To induce tendinitis, it was used a intratendineous injection of collagenase in the right calcaneal tendon. The treatment consisted of daily application of ultrasound + pequi oil or just pequi oil on the tendon. Macroscopic analysis was performed with the pachymeter on 1st, 7th and 14th days. Posteriorly, the rats were sacrificed with an overdose of intravenous barbiturate, then it was dissected and removed the tendon to enable the histological analysis with Hematoxylin & Eosin (HE). Results: There was a reduction in the number of inflammatory cells in the animals treated for 7 days in the groups UST + pequi oil and pequi oil compared to the control, with p <0,001. At 14 days, the group UST + pequi oil showed greater number of fibroblasts than the other groups, with p<0,01. Conclusion: The pequi oil accelerated the tendon repair in the animals and the treatment with US + pequi oil was the most effective because it reached good statistical significance in seven and 14 days.